2017
DOI: 10.1371/journal.pone.0176841
|View full text |Cite|
|
Sign up to set email alerts
|

T1R3 homomeric sweet taste receptor regulates adipogenesis through Gαs-mediated microtubules disassembly and Rho activation in 3T3-L1 cells

Abstract: We previously reported that 3T3-L1 cells express a functional sweet taste receptor possibly as a T1R3 homomer that is coupled to Gs and negatively regulates adipogenesis by a Gαs-mediated but cAMP-independent mechanism. Here, we show that stimulation of this receptor with sucralose or saccharin induced disassembly of the microtubules in 3T3-L1 preadipocytes, which was attenuated by overexpression of the dominant-negative mutant of Gαs (Gαs-G226A). In contrast, overexpression of the constitutively active mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
3
10
0
2
Order By: Relevance
“…For example, homodimers of T1R3 are expressed in mouse pancreatic β -cells and their functionality has been assessed by using sucralose, showing that activation of T1R3 by sucralose upregulates insulin secretion 6062 . It has been reported that mouse adipocytes express functional sweet taste receptor possibly as a T1R3 homomer and stimulation with sucralose or saccharin negatively regulates adipogenesis 63,64 . In rodents, it has been recently demonstrated that T1R3 is expressed in the pulmonary endothelium, where its activation by sucralose protects, in vitro and in vivo , the endothelium from edemagenic agent-induced barrier disruption 65 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, homodimers of T1R3 are expressed in mouse pancreatic β -cells and their functionality has been assessed by using sucralose, showing that activation of T1R3 by sucralose upregulates insulin secretion 6062 . It has been reported that mouse adipocytes express functional sweet taste receptor possibly as a T1R3 homomer and stimulation with sucralose or saccharin negatively regulates adipogenesis 63,64 . In rodents, it has been recently demonstrated that T1R3 is expressed in the pulmonary endothelium, where its activation by sucralose protects, in vitro and in vivo , the endothelium from edemagenic agent-induced barrier disruption 65 .…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-VEGFR2 binding results in PI3K-dependent phosphorylation and activation of Akt resulting in increased endothelial cell proliferation, migration and permeability [ 37 ]. Interestingly, artificial sweeteners have been demonstrated to have opposing effects on Akt phosphorylation, depending on the differentiation stage of the cell and the phosphorylation site investigated [ 38 , 39 ]. In the present study, we demonstrated that sucralose blocked VEGF-induced phosphorylation of Akt at Ser 473 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, other studies have focused on other monosaccharides, particularly fructose [4], and few studies have focused on other natural complex sweeteners, such as honey, brown sugar, steviol glycosides, or the artificial sweetener sucralose [5]. In conditions of persistent intake of sweeteners, some taste receptors type 1 member 2 (T1R2) or member 3 (T1R3) are activated in tongue, intestine, and adipose tissue [6,7,8]. Sugar and artificial sweeteners can bind selectively to one or both receptors in different proportions, and this raises the possibility that sweeteners may influence the metabolism of adipose tissue [9].…”
Section: Introductionmentioning
confidence: 99%